Playing Up - Warner, David and Black, J. S.; Illustrated by Faber, Jules (Australia Simon & Schuster, 2014)
In this second book in the series, Davey wishes he could be as good a cricketer as his older brother Steve, who's always telling him to practise more. And there's nothing else that Davey and his mates like to do more-the classroom is as good as the playground, right? Mr Mudge, the Year 6 teacher and absolute grump, doesn't think so ..
Include Illustrations
Keywords: Australia -- Children's stories -- Cricket stories